Comparing phylogenetics and linear morphometrics to solve the generic assignment of Parabolinella? triarthroides Harrington (Trilobita, Olenidae). (18th August 2017) - Monti, Daniela S.; Confalonieri, Viviana A.
Abstract: The use of different methodological approaches together with an exhaustive qualitative study has helped to recognize important morphological traits to distinguish species in a systematic and phylogenetic framework. Parabolinella triarthroides Harrington, 1938 was described based on two cranidia from the Quebrada de Coquena, Purmamarca, Jujuy province. The generic assignment of P. triarthroides has been questioned by a phylogenetic analysis, which resolves this species as the sister group of Bienvillia Clark, 1924. To explore the generic assignment of this species, a revision of the type material, plus a morphometric analysis including specimens of Parabolinella Brøgger, 1882 and Bienvillia were performed. In addition, the original matrix used in the published phylogeny was reviewed and enlarged, including more species of Bienvillia . Continuous characters were coded in different ways in order to compare how they could affect the ordering of specimens and their phylogenetic relationships. Finally, both methodologies were compared, especially in regard to the behavior of the quantitative characters included in the analyses. From the combined analyses, it is shown that similarities between the cranidium of P. triarthroides and all other Parabolinella species are true homologies instead of a by-product of evolutionary convergence. Therefore, P. triarthroides should be considered a member of this genus. Finally, this study demonstrates that the best strategy for solving systematic problems in groups where the morphological variation is the only source of information (i.e., fossil taxa without living representatives) is the implementation of an integrative approach, combining different methodological techniques and a good description of specimens.